2021
DOI: 10.1002/tox.23353
|View full text |Cite
|
Sign up to set email alerts
|

In vivo hepatoprotective effect of Morinda elliptica stem extract against liver fibrosis induced by thioacetamide

Abstract: Morinda elliptica L. (Rubiaceae) is a phytomedicinal herb, used to treat gastrointestinal complications in Peninsular Malaysia. The study evaluates the in vivo hepatoprotective activity of ethanolic extract of M. elliptica stem in thioacetamide (TAA) induced liver fibrosis in male Sprague Drawly rats. Thirty adult rats were divided into five groups of six rats each. Rats of the normal control group received intraperitoneal injections (i. p.) of vehicle 10% Tween-20, 5 ml/kg, and hepatotoxic group 200 mg/kg TAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…The increase in liver function biomarkers imitates hepatocellular dysfunction. With the consistence of the results of current study increased in liver markers activities and bilirubin level in hepatotoxic group were previously reported by several researchers [18,35,43,46].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The increase in liver function biomarkers imitates hepatocellular dysfunction. With the consistence of the results of current study increased in liver markers activities and bilirubin level in hepatotoxic group were previously reported by several researchers [18,35,43,46].…”
Section: Discussionsupporting
confidence: 85%
“…With the agreement of the results of our investigation enormous numbers of scientists displayed that rat's gavage silymarin or various plant extracts brought the albumin and protein to almost normal levels [15,20,21,25,46,50,51] reported that ethanolic leave extracts of Garuga pinnata can serve as promising herbal medicine for the treatment of both acute and chronic hepatotoxicity due to the presence of avonoids rutin, Outcomes of the existing research showed a decline collagen deposition in pinostrobin fed groups in tissue sections stained with Masson's trichrome dye. Analogous to the results of current study many investigators used innumerable plant extracts con rmed reduction of collagen bers compared to TAA control group [14,16,21,38,41].…”
Section: Discussionsupporting
confidence: 83%
“…This study speculates that EVs may play an important role in the treatment of liver injury by liver stem cells. From the results, we found that the treatment of EVs could inhibit the process of liver fibrosis to a certain extent 10,34–36 . These data prove that LSCs could treat liver fibrosis through EVs.…”
Section: Discussionmentioning
confidence: 55%
“…From the results, we found that the treatment of EVs could inhibit the process of liver fibrosis to a certain extent. 10,[34][35][36] These data prove that LSCs could treat liver fibrosis through EVs. Macrophages are important effector cells of the body's immune response and play an important role in many diseases including tumors, immune system diseases and fibrosis.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, we detected the indicators of autophagy and macrophage polarization and found that when autophagy was inhibited, the expression of M1-type markers was inflammatory responses in liver tissue. 6,11,25 Autophagy is a regulated, dynamic, multistep process aimed at maintaining cellular homeostasis.…”
Section: In Vivo Assays To Verify the Effects Of Macrophage Evs And A...mentioning
confidence: 99%